Maqasid al-Shariah and the value of trust - Altabaa, Homam; Samsudin, Ameelia Husna (2020)
Maqasid al-Shariah refers to the greater and higher purposes or goals that are embedded in the Shariah or Islamic law to realize and protect the virtues or interests (maslahah) of human beings in all aspects of life. This paper seeks to explore the various dimensions of the concept of trust from an Islamic perspective with a special reference to the theory of Maqasid al-Shariah. Trust principally means the belief in the reliability of someone or something to carry out their roles and responsibilities. It is a foundational value in the Islamic system that addresses the lives of individuals and of groups on micro and macro levels. As the implications and effects of trust are important and pervasive, this study serves as a basis to critically realize the value of trust in Islam. Accordingly, the paper presents an overview of Maqasid al-Shariah as a framework that guides Islamic practices before examining the value of trust within this framework. Subsequently the utility of trust in Islam is further explored and assessed through evidence from the Quran and Sunnah.